Formulasi amelioran organik untuk menurunkan kadar salinitas tanah dan meningkatkan pertumbuhan tanaman padi di lahan salin - Aghnia Rahmawati; Fiqriah Hanum Khumairah (University of Insan Cendekia Mandiri, 2023)
Soil salinity is still an obstacle that needs to be managed well on agricultural land located close to shoreline. The purpose of this study was to formulate an organic ameliorant to reduce soil salinity levels and increase the growth of rice plants on saline soils. The study was conducted in Jayamukti Village, Banyusari District, Karawang Regency from March to June 2022. Experiment used factorial randomized block design consisted of two factors with three replications. The first factor was the composition of organic ameliorant consisted of straw compost, husk charcoal, coconut shell biochar, dolomite, and humic acid. The second factor was the dose of organic ameliorant consisted of 0, 1, 2, and 3 tons/ha. The results showed that the application of organic ameliorant formulas in the form of 100% straw compost and 70% straw compost + 20% biochar + 10% dolomite at a dose of 3 tons / ha tended to be able to inhibit the decrease in saline soil acidity (0.15%) and reduce soil salinity levels (3.57%). The composition and dose of organic ameliorant interacted with each other in increasing the growth of rice plants by increasing plant height (40.10 cm) and number of tillers (6.00) compared to plants that were not given organic ameliorant on saline soil. Further research is needed on the efficacy test of the ameliorant formula in the field in increasing the growth and productivity of rice plants in saline land